Osteoblasts Generate Testosterone From DHEA and Activate Androgen Signaling in Prostate Cancer Cells. (18th May 2021) - Moon, Henry H; Clines, Katrina L; O'Day, Patrick J; Al‐Barghouthi, Basel M; Farber, Emily A; Farber, Charles R; Auchus, Richard J; Clines, Gregory A
ABSTRACT: Bone metastasis is a complication of prostate cancer in up to 90% of men afflicted with advanced disease. Therapies that reduce androgen exposure remain at the forefront of treatment. However, most prostate cancers transition to a state whereby reducing testicular androgen action becomes ineffective. A common mechanism of this transition is intratumoral production of testosterone (T) using the adrenal androgen precursor dehydroepiandrosterone (DHEA) through enzymatic conversion by 3β‐ and 17β‐hydroxysteroid dehydrogenases (3βHSD and 17βHSD). Given the ability of prostate cancer to form blastic metastases in bone, we hypothesized that osteoblasts might be a source of androgen synthesis. RNA expression analyses of murine osteoblasts and human bone confirmed that at least one 3βHSD and 17βHSD enzyme isoform was expressed, suggesting that osteoblasts are capable of generating androgens from adrenal DHEA. Murine osteoblasts were treated with 100 nM and 1 μM DHEA or vehicle control. Conditioned media from these osteoblasts were assayed for intermediate and active androgens by liquid chromatography–tandem mass spectrometry. As DHEA was consumed, the androgen intermediates androstenediol and androstenedione were generated and subsequently converted to T. Conditioned media of DHEA‐treated osteoblasts increased androgen receptor (AR) signaling, prostate‐specific antigen (PSA) production, and cell numbers of the androgen‐sensitive prostate cancer cell lines C4‐2B and LNCaP. DHEA did not induce AR signaling in osteoblasts despite AR expression in this cell type. We describe an unreported function of osteoblasts as a source of T that is especially relevant during androgen‐responsive metastatic prostate cancer invasion into bone. © 2021 American Society for Bone and Mineral Research (ASBMR). This article has been contributed to by US Government employees and their work is in the public domain in the USA.